2023
DOI: 10.5937/jomb0-35933
|View full text |Cite
|
Sign up to set email alerts
|

Comparison urine neutrophil gelatinase - associated lipocalin with standard parameters in monitoring activity Lupus nephritis: Class IV

Abstract: Introduction:  Lupus nephritis (LN) is one of the most serious complications in the development of systemic lupus erythematosus, that can adversely affect the course and prognosis of this autoimmune disease. Therefore, monitoring the effect of applied therapy, achieving remission, or monitoring LN activity is still a great challenge for nephrologists. This study aimed to compare the urinary  neutrophile gelatinase associated lipocalin  (u/NGAL)   with traditionally accepted parameters for LN activity to indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In the study, SII was constructed to predict the recurrence and survival for hepatocellular carcinoma patients (7). In the recent years, more and more studies use SII to explore the association of systemic in ammation with the subjects' healthy status (lupus nephritis (21), psoriasis (22), arthritis (23) and NAFLD (19,24,25)). One study, based on NHANES, revealed that ln-transformed SII was an independent risk factor for NAFLD risk (de ned by a US Fatty Liver Index (USFLI) score exceeding 30), and the corresponding OR and 95%CI was 1.46 (1.27, 1.69) (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, SII was constructed to predict the recurrence and survival for hepatocellular carcinoma patients (7). In the recent years, more and more studies use SII to explore the association of systemic in ammation with the subjects' healthy status (lupus nephritis (21), psoriasis (22), arthritis (23) and NAFLD (19,24,25)). One study, based on NHANES, revealed that ln-transformed SII was an independent risk factor for NAFLD risk (de ned by a US Fatty Liver Index (USFLI) score exceeding 30), and the corresponding OR and 95%CI was 1.46 (1.27, 1.69) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Timely diagnosis and treatment of LN allow not only the recovery of kidney function but also prevent life-threatening complications. This is also the reason for many studies examining the role of various markers that would enable the diagnosis and monitoring of LN activity, the occurrence of potential relapses, and the right time to reduce the dose of immunosuppressive therapy [1] [2] [3] [4] [5] . Potential markers whose determination is not complicated, which do not require a long process, and are available in everyday clinical practice are significant.…”
Section: Introductionmentioning
confidence: 99%